Pengaruh Financial Distress, Profitabilitas, Pertumbuhan Penjualan dan Leverage Terhadap Nilai Perusahaan di BEI - Karo Sekali, Figo Valentino; Butar-butar, Hotlan; Siregar, Selamat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and analyze how Financial Distress, Profitability, Sales Growth and Leverage affect Company Value in Raw Materials Sector Companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The variables used in this study, the independent variable (X) consists of Financial Distress measured by (Almant Z-Score Period III), Profitability measured by (ROA), Sales Growth measured by (SG) and Leverage measured by (DAR), and the dependent variable (Y) is Company Value proxied by PBV. The sample in this study was obtained by the purposive side method. Based on the criteria and data processing process that have been set, 11 companies were determined as research samples. The data analysis technique used is multiple linear regression. The results of this study state that partially, Financial distress (FD) does not have a significant effect on company value, Profitability has a significant effect on company value, sales growth has a significant effect on company value and Leverage does not have a significant effect on company value. Simultaneously, Financial distress, Profitability, Sales growth and Leverage have a significant effect on company value.